Perilaku Muzakki dalam Menyalurkan Zakat di Era Digital - Nenie Sofiyawati; Siti Nur Halimah (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2022)
Preaching zakat to muzakki requires understanding the preferences of muzakki in distributing zakat. This study aims to formulate the preferences of muzakki in distributing zakat in the digital era. The literature review of 11 scientific articles was analyzed with Philip Kotler's consumer behavior theory. Based on the literature review, it can be formulated the tendency of muzakki's preferences in distributing zakat: directly to mustahik, mosque amil, LAZ amil, fundraising applications, and LAZ digitization. The encouragement of conventional zakat distribution behavior is influenced by cultural, social, psychological, and personal factors. Meanwhile, digital-based muzakki behavior is influenced by social, psychological, and personal factors. Zakat managers need to provide digital and conventional zakat payment channels. Muzakki, with the support of a digital ecosystem, can be optimized for digitization. Muzakki, who are not yet supported by the digital ecosystem, can optimize conventional methods.